Scales and government in the study of the new argentine right (Estudios Sociales, 2021)
This article analyzes the political recruitment and the ways of doing politics that were consolidated in the state social assistance during the PRO and Cambiemos goverments at three different levels of government: City of Buenos Aires, province of Buenos Aires and the level national. From a multi-level analysis that included a database with 151 trajectories and interviews with 32 officials, showed the pragmatism that the new Argentine right had in the social-welfare government where, between 2007 and 2019, they developed a style of social management concerned with the proximity of the state and committed to the political project of the PRO and the Cambiemos Alliance within the framework of a heterogeneity of proposals formulated for territories with diverse challenges.
Keywords: tate social assistance; political recruitment; Cambiemos; PRO; Scales